Volumetric laser endomicroscopy and optical coherence tomography in Barrett’s esophagus: a systematic review and meta-analysis - Rodriguez, Maria Auxiliadora Chóez; de Moura, Diogo Turiani Hourneaux; Ribeiro, Igor Braga; Bernardo, Wanderley Marques; Morita, Flavio Hiroshi Ananias; Marques, Sergio Barbosa; Sakai, Paulo; de Moura, Eduardo Guimarães Hourneaux (Endoscopy International Open, 2019)
Background and study aims Endoscopic imaging of Barrett’s esophagus (BE) with advanced technologies, such as optical coherence tomography (OCT) and volumetric laser endomicroscopy (VLE), allows targeted biopsies and may reduce the number of random biopsies to detect esophageal neoplasia in the early stages during endoscopic BE surveillance. The aim of this study was to evaluate the accuracy of OCT and VLE in diagnosis of intestinal metaplasia, dysplasia, and high-grade dysplasia (HGD), and intramucosal carcinoma (IMC) in BE.Patients and methods In this systematic review and meta-analysis, the primary outcome measure was diagnostic accuracy of OCT and VLE, in comparison with the gold standard. In the meta-analysis, we calculated sensitivity, specificity, positive likelihood ratio (LR+), negative likelihood ratio (LR-), and diagnostic odds ratio (DOR) for both methods. We performed analyses by patient and by lesion. Results We evaluated 14 studies involving a collective total of 721 patients and 1565 lesions. In the analysis by lesion, VLE showed a pooled sensitivity, specificity, LR+, LR−, DOR, and SROC AUC of 85 %, 73 %, 3.2, 0.21, 15.0, and 0.87, respectively, for detection of HGD/IMC. In the analysis by lesion for detection of HGD/EAC, OCT showed a pooled sensitivity, specificity, LR+, LR−, DOR, and summary receiver operating characteristic area under the curve of 89 %, 91 %, 9.6, 0.12, 81.0, and 0.95, respectively. The accuracy of OCT in identifying intestinal metaplasia showed a pooled sensitivity, specificity, LR+, LR−, and DOR of 92 %, 81 %, 5.06, 0.091, and 55.58, respectively.Conclusion OCT- and VLE-guided targeted biopsies could improve detection of dysplasia and neoplasia. Further studies could determine whether the use of such biopsies might replace the current protocol.